The Effect of Bay Leaf Extract (Syzygium polianthum) Against Cholesterol Regulation in Hypercholesterolemic Rats - Lusia Hayati; Rachmat Hidayat (Eureka Herba Indonesia, 2020)
Cholesterol is an important precursor that plays a role in the production and regulation of various sterol group compounds, especially steroid hormone compounds, androgen hormone compounds, cortisol compounds, and estrogen compounds. This herb is known to have the effect of improving glucose regulation by increasing glucose intake into cells and tissues. Its ability to improve cell and tissue metabolism is mediated by the content of secondary metabolite compounds. This ability is believed to have the potential to improve cholesterol regulation. Bay leaf extract is effective in lowering cholesterol levels through regulation of Acetyl CoA production.